2016
DOI: 10.3390/w8040153
|View full text |Cite|
|
Sign up to set email alerts
|

Development of a Watershed-Scale Long-Term Hydrologic Impact Assessment Model with the Asymptotic Curve Number Regression Equation

Abstract: Abstract:In this study, 52 asymptotic Curve Number (CN) regression equations were developed for combinations of representative land covers and hydrologic soil groups. In addition, to overcome the limitations of the original Long-term Hydrologic Impact Assessment (L-THIA) model when it is applied to larger watersheds, a watershed-scale L-THIA Asymptotic CN (ACN) regression equation model (watershed-scale L-THIA ACN model) was developed by integrating the asymptotic CN regressions and various modules for direct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Generally, various hydrological models, such as the Soil and Water Assessment Tool (SWAT), the Hydrological Simulation Program-Fortran (HSPF), and the watershed-scale Long-Term Hydrologic Impact Assessment Model (watershed-scale L-THIA), have been developed and utilized to predict river discharge and dam inflow [5][6][7]. The hydrological model is one of the most popular methods to predict water cycle components by reflecting the physical mechanisms of the hydrological process in the watersheds.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, various hydrological models, such as the Soil and Water Assessment Tool (SWAT), the Hydrological Simulation Program-Fortran (HSPF), and the watershed-scale Long-Term Hydrologic Impact Assessment Model (watershed-scale L-THIA), have been developed and utilized to predict river discharge and dam inflow [5][6][7]. The hydrological model is one of the most popular methods to predict water cycle components by reflecting the physical mechanisms of the hydrological process in the watersheds.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the watershed-scale L-THIA ACN model, developed by Ryu et al [27], was enhanced by developing a field pollutant load estimation module and incorporating the instream QUAL2E model, in order to simulate pollutant loads at a watershed scale. Comparison of the simulated results of this L-THIA ACN-WQ model with observed values from two watersheds in These results show that the watershed-scale L-THIA ACN-WQ model can simulate not only streamflow but also pollutant loads at a watershed with less input data required than for complex watershed-scale models.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 802 responses, a majority of the respondents (78%) believed that the conservation of cultural and religious values of temples is important or very important. Respondents' environmentally responsible behaviors in national parks (ERB) were asked using 12 five-point scale items developed by Ryu et al [46] and the results of exploratory factor analysis (EFA) confirmed a single factor. The variable of ERB was created based on the aggregation of these items.…”
Section: Profiles Of the Respondents' Perception And Behaviorsmentioning
confidence: 99%